Byron and romanticism - McGann, Jerome J. (Cambridge University Press, 2002)
This collection of essays represents twenty-five years of work by a leading critic of Romanticism in general and Byron in particular. It demonstrates McGann's evolution as a scholar, editor, critic, theorist, and historian, and his engagement with the main schools of literary criticism since the advent of structuralism in the 1960s. Many of these essays have previously been available only in specialist scholarly journals. Now for the first time McGann's important and influential work on Byron can be appreciated by new generations of students and scholars